Reducing Training Volume during Tapering Improves Performance in Taekwondo Athletes - Carazo Vargas, Pedro (2018)
There is a lack of evidence on periodization models in Taekwondo. Purpose: This study evaluated the effects of reducing the training volume during tapering on fitness and motor performance variables in Taekwondo athletes. Methods: Volunteers were eight male (21.3 ± 3.62 yr., 75.5 ± 16.3 kg body weight, 174.4 ± 7.0 cm body height, 17.5 ± 8.4% body fat mass, VO2max = 53.5 ± 5.0 ml kg-1 min-1) and four female (19.5 ± 1.3 yr., 51.7 ± 2.25 kg body weight, 160.6 ± 5.1 cm body height, 26.5 ± 6.1% body fat mass, VO2max = 45.5 ± 4.1 ml kg-1 min-1) Taekwondo college athletes. The training intervention included a 10-week standardized overload phase for all participants, followed by three weeks of tapering. During the tapering phase, participants were randomly assigned to either a condition consisting of maintaining the training volume or a condition where training volume was linearly-reduced by 50%. Physical fitness and motor performance variables were measured before and after tapering. Results: No statistical significant group by time interactions were found on any performance variable (P>.05). Main effects analyses showed improved performance in muscular strength (P=.01), squat (P=.01), counter-movement (P=.01), arms counter-movement (P=.01) and drop (P=.01) jumps, and two kicking drills (kicking response time, P=.03; kicking movement time, P=.04). The 50% training volume tapering strategy elicited higher effect sizes and %H than the no reduction strategy for all performance variables. Conclusion: A training model using block periodization allowed improvements in Taekwondo fitness and motor performance variables regardless of the three-week tapering strategy used.